Predictive role of hand and foot dimensions for stature estimation in the Malaysian population - Mohamadon, Emizam; Alias, Aspalilah; Abu Bakar, Siti Noorain; Mohd Nor, Faridah; Mohamed, Aishah; Rosman, Daaniyal Reesha; Mohhan, Kothai; Kunasegaran, Lakhneswaran; Jarry, Sonia (Taylor and Francis Ltd., 2024)
Estimation of stature plays a significant role in establishing personal identity in forensic anthropology. The objective is to derive specific population regression equations to estimate stature from hand and foot measurements in the Malaysian population. A prospective cross-sectional study was done with 400 staffs and students, who were randomly chosen from Universiti Kebangsaan Malaysia Medical Centre (UKMMC) and ranged from 19 to 60 years old. The subjects comprised 200 males and 200 females (257 Malay, 112 Chinese and 31 Indian). Eleven parameters, such as hand length 1, hand length 2, hand length 3, hand length 4, hand length 5, hand length, palm length, hand breadth, maximum hand breadth, foot breadth and foot length were measured twice by measuring tape and Vernier callipers, and were averaged. Results revealed that the parameters exhibited a significant difference between sexes and ethnic groups (p < 0.05). The relative TEM was 0.7 and 1.37% for intra- and inter-observational analyses, respectively, which were acceptable for measurement accuracy. Paired t-tests showed close approximation between estimated and true stature. Thus, the regressions could be used for stature estimation in the Malaysian population. Further study is needed to evaluate and validate the results for future use.